2004
DOI: 10.1007/s00404-003-0590-x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal removal of prolapsed pedunculated submucous myoma: a short, simple, and definitive procedure with minimal morbidity

Abstract: Vaginal myomectomy is the treatment of choice for prolapsed pedunculated submucous myoma. The associated morbidity is minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 7 publications
0
64
0
3
Order By: Relevance
“…As the age of marriage and childbearing increases in developing countries, the prevalence of fibroid pregnancies and its complications could rise. Vigilance is necessary to detect and manage myomas (especially the submucous and intramural variants) before or during pregnancy as this has been shown to reduce morbidities 6 .…”
Section: Discussionmentioning
confidence: 99%
“…As the age of marriage and childbearing increases in developing countries, the prevalence of fibroid pregnancies and its complications could rise. Vigilance is necessary to detect and manage myomas (especially the submucous and intramural variants) before or during pregnancy as this has been shown to reduce morbidities 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the operating time, anesthetic exposure and intraoperative bleeding. Golan et al, reported in their series that the technique was successful in 95.6% of the patients and all had uneventful recoveries [5]. The associated morbidity was minimal and the recovery period was very short as the case we presented [5].…”
Section: Discussionmentioning
confidence: 57%
“…Imaging modalities especially ultrasonography and MRI play an important role in the management of patients with prolapsed pedinculated leiomyomas especially for the pre-operative localization of leiomyomas and surgical planning for myomectomy. Most authors regard this surgical procedure as the safe and initial treatment for prolapsed pedunculated submucous myomas [5,6]. It reduces the operating time, anesthetic exposure and intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended treatment-of-choice for prolapsed, pedunculated fibroids is a vaginal myomectomy [6]. Although the median diameter of fibroids removed vaginally and described is about 5 cm, some recent reports describing a vaginal myomectomy of tumours exceeding 7 cm can be found [7].…”
Section: Discussionmentioning
confidence: 99%